Towards a fundamental understanding of the effects of surface conditions on fatigue resistance for safety-critical AM applications. (July 2020) - Zeng, G-W.; Monu, M.C.; Lupton, C.; Lin, B.; Tong, J.
Highlights: Cyclic behaviour in High Cycle Fatigue regime studied for 17-4PH steel produced by AM. Two deformation modes identified from notches and surface roughness features. Ratchetting seems to be predominant at high stresses whilst shakedown at low stresses. Similar behaviour found in two other material types using the FE analysis. Abstract: Fatigue behaviour in High Cycle Fatigue (HCF) regime has been studied in a 17–4 PH steel produced by an Additive Manufacturing (AM) technique, Selective Laser Melting (SLM). The research was prompted by increasing demands of AM techniques for safety-critical engineering applications. One of the main challenges in as-built AM parts is surface roughness, which gives rise to early crack initiation due to stress concentration leading to fatigue failure. This classical problem has been treated empirically in the past, using mainly stress-based approaches. In this work, we studied the cyclic behaviour of materials at the notch root of typical notch sizes in three material types using the finite element analysis with appropriate material models. Two distinct deformation modes are found: Shakedown or ratchetting, dependent on the applied load level. Selected critical surface locations in a specimen produced by SLM were also examined and the results are found to be consistent with those from the idealised notches. The results shed light on the fatigue damage mechanisms in HCF regime, which may be useful in AM material design and life management.